Iron Mettle: Unveiling an Unusual Incidental Case Report of Esophageal Ulcer - Akshi Raj; Mangesh Londhe; Yogesh Bade; Madhuri Singh; Charusheela Gore; Anuj Sharma (Case Reports in Gastroenterology)
Introduction: Erosive damage to the upper gastrointestinal (GI) tract caused by therapeutic oral iron supplements is relatively uncommon. While such injuries are frequently linked to overdoses of oral iron, they can also occur with doses within the standard therapeutic range. Cases have highlighted GI complications caused by iron, predominantly involving the stomach and sometimes the esophagus. During absorption, iron is initially processed as ferrous iron, which, when bound to proteins, can lead to cellular injury. Additionally, ferric iron exerts a corrosive effect on the GI mucosa and disrupts cellular processes by generating free radicals and triggering lipid peroxidation. Case Presentation: A 55-year-old female with dysphagia, pain, and anorexia showed linear to circumferential ulcers covered with white slough extensively around central esophagus with thickened and erythematous mucosa with focal erosions on esophagogastroduodenoscopy. Conclusion: This case highlights a rare case report of iron-induced esophageal ulcer found incidentally and the significance of acknowledging that iron preparations can harm the esophageal mucosa, especially in an Indian population where anemia is fairly predominant.